Efficient removal of silver ions from wastewater via chelation with dithiooxamide-functionalized polymeric adsorbent - Abdullah S. Al-Bogami; Abdullah Akhdhar; Dina A. Tolan; Mohamed H. Ismael; Emad A. Elshehy; Waleed A. El-Said (PLoS ONE, 2025)
This study investigates Ag(I) adsorption on a dithiooxamide/glutaraldehyde resin (DTG-R) using both experimental and theoretical approaches. Characterization confirmed the resin’s porous structure and sulfur/nitrogen active sites. Batch experiments revealed high Langmuir capacity (27.2 mmol/g at 25°C), with kinetics following a pseudo-second-order model ( R 2 > 0.99), indicating chemisorption. Thermodynamic analysis showed endothermic ( ΔH° = 121.25 kJ/mol), spontaneous adsorption ( ΔG° = −12.8 to −17.3 kJ/mol), driven by entropy gains ( ΔS° = 449.9 J/mol.K) from Ag(I) dehydration and polymer swelling. DFT calculations demonstrated preferential Ag(I) binding to deprotonated sulfur (S–Ag: 2.50–2.60 Å, bond order: 0.76–0.86) over nitrogen, with mononuclear complexes being most stable ( ΔE = −175.6 kcal/mol). The resin exhibited high selectivity, reusability of 96% efficiency over five cycles, and optimal performance at pH 5.75. NBO analysis revealed charge transfer to Ag(I) (partial charge less than +1), while binding energy trends explained the observed temperature-dependent capacity. DTG-R combined high capacity, rapid kinetics, and molecular-level affinity for Ag(I) make it better than existing adsorbents for industrial wastewater remediation. This work bridges macroscopic adsorption properties with quantum-chemical mechanisms, offering a template for rational adsorbent design.